Secukinumab administration by pre‐filled syringe: efficacy, safety and usability results from a randomized controlled trial in psoriasis (FEATURE). (1st February 2015) - Blauvelt, A.; Prinz, J.C.; Gottlieb, A.B.; Kingo, K.; Sofen, H.; Ruer‐Mulard, M.; Singh, V.; Pathan, R.; Papavassilis, C.; Cooper, S.; ,
Summary: Background: Secukinumab, a fully human anti‐interleukin‐17A monoclonal antibody, demonstrated efficacy and safety in moderate‐to‐severe plaque psoriasis when administered via subcutaneous injection. Self‐administration by pre‐filled syringe (PFS) can offer patients clinical benefits of a drug, with increased convenience. Objectives: To assess efficacy, safety and usability of secukinumab administration via PFS in subjects with moderate‐to‐severe plaque psoriasis. Materials and methods: Subjects in this phase 3 trial were randomized 1 : 1 : 1 to secukinumab 300 or 150 mg or matching placebo. Results to week 12 are presented here. Each treatment was delivered using a PFS once weekly to week 4, and again at week 8. Co‐primary endpoints were secukinumab superiority over placebo for week 12 PASI 75 (≥ 75% reduction in Psoriasis Area and Severity Index) and IGA mod 2011 (2011 modified Investigator's Global Assessment) 0/1 response rates. Secondary endpoints included PFS usability, determined by observer rating of successful, hazard‐free self‐injection and subject rating of acceptability by the Self‐Injection Assessment Questionnaire (SIAQ). Results: Co‐primary endpoints were met, with demonstration of superiority for each secukinumab dose vs. placebo at week 12 (PASI 75: 75·9%, 69·5% and 0% for secukinumab 300 mg, 150 mg and placebo; IGA mod 2011 0/1: 69·0%, 52·5% and 0%, respectively; P < 0·0001 for all comparisons vs. placebo). PFS usability was high: 100% of subjects successfully self‐administered treatment at week 1, and subjects reported high SIAQ‐assessed acceptability of the PFS throughout the trial. No new/unexpected safety signals were observed. Conclusions: Secukinumab administration by PFS was effective, with an acceptable safety profile and high usability. The PFS provides a reliable, convenient form of secukinumab administration in subjects with moderate‐to‐severe plaque psoriasis.